2018
DOI: 10.1016/j.jcin.2018.01.262
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes After Percutaneous Closure of Ostium Secundum Atrial Septal Defect in the Young

Abstract: Transcatheter ASD closure using Amplatzer Septal Occluder is safe in children with a minimal rate of periprocedural complications and a favorable long-term outcome, especially with no death or cardiac erosion despite a substantial proportion of large defects. Children ≤15 kg and those with large ASDs had a greater risk of complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 36 publications
6
58
1
3
Order By: Relevance
“…The IMPACT review of 1,564 ASD device closures demonstrated no residual leak (>3 mm) in GSO implants, 0.6% in the Helex Septal Occluder, and 1.8% with the Amplatzer Septal Occluder (ASO). Importantly, patients with deficient superior rim accounted for 40% of the IMPACT cohort, similar to that reported in the national French study (28.3%), but much higher than the prospective, multicenter U.S. study of the ASO (11.5%) . One approach that we have utilized in specific ASD morphology (i.e., larger defects with deficient retroaortic rim) is to implant a larger GSO if the septal length and left atrium can safely accommodate the device.…”
Section: Discussionmentioning
confidence: 46%
“…The IMPACT review of 1,564 ASD device closures demonstrated no residual leak (>3 mm) in GSO implants, 0.6% in the Helex Septal Occluder, and 1.8% with the Amplatzer Septal Occluder (ASO). Importantly, patients with deficient superior rim accounted for 40% of the IMPACT cohort, similar to that reported in the national French study (28.3%), but much higher than the prospective, multicenter U.S. study of the ASO (11.5%) . One approach that we have utilized in specific ASD morphology (i.e., larger defects with deficient retroaortic rim) is to implant a larger GSO if the septal length and left atrium can safely accommodate the device.…”
Section: Discussionmentioning
confidence: 46%
“…A total of 91 consecutive pediatric patients (38 males; median age 5.0 years [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]; median weight 20 kg ) underwent successful GSO implantation at least 1 year before study enrollment. Patients' baseline characteristics are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Refinements of the devices and materials have contributed to greater procedural safety and facilitated percutaneous treatment even in more complex lesions and younger infants . Despite excellent results, potential serious device‐related complications remain worrying, like cardiac erosion, device embolization, thromboembolic events, significant rhythm or conductance disturbance, as well as device fatigue failure resulting in instability and fragmentation . The patch‐like Gore devices (W.L.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Además, la persistencia de hemocultivos positivos o de clínica séptica, a pesar del tratamiento médico, sería indicación relativa de retirada del dispositivo. 6 En el caso presentado, dado el buen estado general del paciente, la ausencia de inestabilidad del dispositivo y la ausencia de complicaciones con clara indicación quirúrgica, se optó por un manejo conservador con tratamiento antibiótico endovenoso. Nuestro caso es el primero publicado, ya que, tras una exhaustiva revisión bibliográfica, no se han encontrado otros reportes en la población pediátrica en los que se realice un manejo exitoso totalmente conservador, sin retirada del dispositivo.…”
Section: Figura 2 Ecocardiografía Transtorácica 2d No Se Aprecian Iunclassified